Pregnancies during and after trastuzumab and/or lapatinib in patients with human epidermal growth factor receptor 2–positive early breast cancer: Analysis from the NeoALTTO (BIG 1‐06) and ALTTO (BIG 2‐06) trials. Issue 2 (18th October 2018) - Lambertini, Matteo; Martel, Samuel; Campbell, Christine; Guillaume, Sébastien; Hilbers, Florentine S.; Schuehly, Uwe; Korde, Larissa; Azim, Hatem A.; Di Cosimo, Serena; Tenglin, Richard C.; Huober, Jens; Baselga, José; et al.
Abstract : Background: Limited data exist on the safety of using anti–human epidermal growth factor receptor 2 (HER2) targeted agents during pregnancy. To date, only retrospective studies have assessed the prognosis of patients with a pregnancy after prior early breast cancer, with no data in HER2‐positive patients. Methods: The Neoadjuvant Lapatinib and/or Trastuzumab Treatment Optimization (NeoALTTO) trial and the Adjuvant Lapatinib and/or Trastuzumab Treatment Optimization (ALTTO) trial were randomized phase 3 trials for patients with HER2‐positive early breast cancer. In both trials, pregnancy information was prospectively collected. Pregnancy outcomes were compared between patients unintentionally exposed to trastuzumab and/or lapatinib during gestation (the exposed group) and those who became pregnant after trastuzumab and/or lapatinib completion (the unexposed group). In the ALTTO trial, disease‐free survival (DFS) was compared between pregnant patients and those aged 40 years or younger without a subsequent pregnancy via an extended Cox model with time‐varying covariates to account for a guarantee‐time bias. Results: Ninety‐two patients (12 in the exposed group and 80 in the unexposed group) had a pregnancy: 7 in the NeoALTTO trial and 85 in the ALTTO trial. Seven patients (58.3%) in the exposed group and 10 patients (12.5%) in the unexposed group opted for an induced abortion; in the unexposed group, 10 patients (12.5%) had a spontaneous abortion. No pregnancy/delivery complications were reported for the remaining cases, who successfully completed their pregnancy, with the exception of 1 fetus with trisomy 21 (Down syndrome). No significant difference in DFS (adjusted hazard ratio, 1.12; 95% confidence interval, 0.52‐2.42) was observed between young patients with a pregnancy (n = 85) and young patients without a pregnancy (n = 1307). Conclusions: For patients with HER2‐positive early breast cancer, having a pregnancy after treatment completion appears to be safe without compromising fetal outcome or maternal prognosis. Abstract : For patients with human epidermal growth factor receptor 2–positive early breast cancer, having a pregnancy after treatment completion appears to be safe without compromising fetal outcome or maternal prognosis. A short, unintentional exposure to trastuzumab and/or lapatinib during gestation does not seem to affect newborn outcomes upon treatment discontinuation, although few live births are described for these patients.